Observations of Anomalous Microwave Emission from HII Regions - Clive Dickinson (Advances in Astronomy)
I give a summary of the observations of Anomalous Microwave Emission (AME) from HII regions. AME has been detected in, or in the vicinity of, HII regions. Given the difficulties in measuring accurate SEDs over a wide range of frequencies and in complex environments, many of these detections require more data to confirm them as emitting significant AME. The contribution from optically thick free-free emission from UCHII regions may be also be significant in some cases. The AME emissivity, defined as the ratio of the AME brightness to the 100 μm brightness, is comparable to the value observed in high-latitude diffuse cirrus in some regions, but is significantly lower in others. However, this value is dependent on the dust temperature. More data, both at high frequencies (>~5 GHz) and high resolution (~1′ or better) is required to disentangle the emission processes in such complex regions.